Implication of HLA-DMA Alleles in Corsican IDDM. Issue 3 (17th June 2013) - Cucchi-Mouillot, P.; Lai, S.; Carcassi, C.; Sorba, P.; Stuart-Simoni, M.; Amoros, J.-P.; Genetet, B.; Haras, D.; Contu, L.
Abstract : The HLA-DM molecule catalyses the CLIP/antigen peptide exchange in the classical class II peptide-binding groove. As such, DM is an antigen presentation regulator and may be linked to autoimmune diseases. Using PCR derived methods, a relationship was revealed between DM gene polymorphism and IDDM, in a Corsican population. The DMA*0101 allele was observed to confer a significant predisposition to this autoimmune disease while the DMA*0102 allele protected significantly. Experiments examining polymorphism of the HLA-DRB1 gene established that these relationships are not a consequence of linkage disequilibrium with HLA-DRB1 alleles implicated in this pathology. The study of the DMA gene could therefore be an additional tool for early IDDM diagnosis in the Corsican population.